1984
DOI: 10.1159/000466194
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Nonhemolytic Transfusion Reactions

Abstract: This study was undertaken to document the incidence of immediate, nonhemolytic transfusion reactions and to identify a technique or set of techniques that would best identify the different causes of these reactions. A variety of tests were employed to detect lymphocyte, granulocyte, platelet and anti-IgA antibodies. During this study 26,318 units of blood components were transfused on 5,030 occasions. 191 immediate, nonhemolytic reactions were experienced giving an incidence per unit of 0.73%. Blood specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 10 publications
1
12
1
Order By: Relevance
“…It has been known for a long time that transfusion of blood components may cause febrile reactions due to leukocyte [8] or platelet antibodies in patients who had received previous transfusions. In the patients studied by Decary et al [3], 64% of patients with nonhemolytic transfusion reactions had leukocyte antibodies as compared to 30% of control patients. De Rie et al [1] further characterized antibodies as human leukocyte antigen (HLA-), platelet-and granulocyte antibodies in patients with febrile reactions.…”
Section: Febrile Non-hemolytic Transfusion Reactionsmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been known for a long time that transfusion of blood components may cause febrile reactions due to leukocyte [8] or platelet antibodies in patients who had received previous transfusions. In the patients studied by Decary et al [3], 64% of patients with nonhemolytic transfusion reactions had leukocyte antibodies as compared to 30% of control patients. De Rie et al [1] further characterized antibodies as human leukocyte antigen (HLA-), platelet-and granulocyte antibodies in patients with febrile reactions.…”
Section: Febrile Non-hemolytic Transfusion Reactionsmentioning
confidence: 90%
“…Their true incidence has therefore been difficult to assess. Decary et al [3] estimated the incidence for nonhemolytic transfusion reactions by 0.4% (of products transfused) in patients receiving platelet concentrates; probably, most of these reactions were febrile reactions. Enright et al [4] reported a rise in temperature in 0.3% of transfusions, but they found transfusion reactions in 1.6% of transfusions if chills with rigors were included in the analysis.…”
Section: Febrile Non-hemolytic Transfusion Reactionsmentioning
confidence: 99%
“…In fact, they stimulate the production of alloantibodies directed against both HLA and leukocyte-specific anti gens [1][2][3] that in turn can be the cause of the febrile transfusion reaction [4,5] and of refractoriness to platelet transfusion [6,7]. Moreover, some viruses, such as cyto megalovirus (CMV), can be transmitted by leukocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Wolf and Canale [6] detailed a fatal reaction to a red cell transfusion in a multitransfused thalassémie child with lymphocytotoxic HLA antibodies. Several recent studies have shown that the most common ly found recipient antibodies associated with nonhemo lytic febrile transfusion reactions are not directed towards granulocyte antigens but are lymphocytotoxic, directed against HLA antigens [5,8,9], Interdonor red cell incompatibility in the Kell antigen system has caused reactions of variable severity [19][20][21][22][23]. Interdonor reactions caused by RBC transfusions have been described in which the transfusion of Kell-negative red cells with Kell antibody in donor plasma at the same time as another unit of Kell-positive red cells has caused a hemolytic transfusion reaction when both units were transfused to a Kell-negative patient [19,20].…”
Section: Discussionmentioning
confidence: 99%